Verrucose tuberculosis cutis associated with chronic monoartritis of knee in a patient with HIV infection - Otivo, Raul Montalvo; Ramirez Alfaro, Jean Piere; Ortiz, Raul Gomez (International Journal of Research in Dermatology, 2020)
Bone component involvement is an atypical form of extrapulmonary mycobacterium tuberculosis and it is rare that it previously affects the skin, its diagnosis is difficult. Lipoarabinomannan (LAM) is a component of the cell walls of mycobacteria, present in some people with active tuberculosis, the test is simple and shows results in twenty minutes, but is not validated in immunocompetent patients. We present the case of a 65 year old man, diagnosed with verrucous tuberculosis and subsequent tuberculous monoarthritis of the left knee with positive analysis of lipoarabinomannan in urine and ELISA for non-reactive HIV with a good clinical response to the treatment of tuberculosis.